Final Phase of Mir Bezanjo’s political struggle (Federalism v/s Regionalism) - Bakht, Nadir (Al-Burz, 2009)
The replacement of Bhutto Government by Zia’s Martial law brought many changes in the administrative and political system of Pakistan. Mir Bezanjo was released on bail from Hyderabad Conspiracy case, he applied on 6th December 1977. There was another breakthrough in the Hyderabad conspiracy case when on 1st January 1978 General Zia-ul-Haq, the chief Martial Law Administrator dis abandoned the Hyderabad. Tribunal and ordered to release all the accused. He also declared an amnesty for those who had left their homes during the disturbances in Balochistan. These developments were warmly appreciated in Balochistan Bezanjo and his old colleagues Khair Bakhsh Marri was also released on 4th January, 1978 from Hyderabad Jail. He stayed for quit a sometime in Quetta Balochistan and then on 11th November 1978 left for England. Sardar Atta Ullah Mengal also flew to England in the middle of 1979. Thus the Political scene of Balochistan was a bit changed, at least Stagnation, if not peace, Could be seen in the politics of Balochistan.